Penentuan Tingkat Kepentingan Email dengan menggunakan Metode K-Nearest Neighbor (Studi Kasus PT Green Air Paciffic Surabaya) - Ade Wahyu Muntizar; Bayu Rahayudi; Indriati Indriati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Email is one of the digital means of communication that has existed since the beginning of internet development and is currently being used popularly. Email is an important means of communication, including for PT Green Air Pacific Surabaya. PT Green Air Pacific Company is a private company engaged in logistics. Because it is engaged in logistics, most of its operations use email as a medium of communication and information. In a day messages received via email can reach 700 messages. Incoming email messages are also not all-important for company productivity, so the increasing number of incoming email messages can actually make it difficult to process company email messages. Based on these problems in this study, an email classification system was made based on its usefulness and importance where the method used was the K-Nearest Neighbor (KNN) classification method. The results of the email classification system based on its importance using the KNN method (a case study of PT Green Air Pacific) show that the highest F-Measure is located at k= 3 and k= 4, which is 98.734, and with the K-Fold Cross Validation data validation method, the F results are obtained.-The highest measure is 100%.